The Unwelcome Guest: Strongyloides stercoralis Hyperinfection in a Patient With Steroid-Dependent Asthma–COPD Overlap Syndrome (ACOS)—A Case Report and Review of Literature - Rafael Miret; Jose M. Acosta-Rullan; Alfredo Toll; Grayson Honeycutt; Manjot Malhi; Christian Almanzar Zorrilla; Raiko Diaz; Mauricio Danckers; Daniel Zapata (Case Reports in Pulmonology)
Strongyloides stercoralis is a soil-transmitted roundworm nematode estimated to affect over 600 million people worldwide. Hyperinfection syndrome (HS) has been described in immunosuppressed patients. Our case highlights a rare manifestation of HS due to Strongyloides stercoralis causing acute respiratory failure in an asthma–COPD overlap syndrome (ACOS) patient on chronic corticosteroid therapy. A 63-year-old woman with diabetes, chronic obstructive pulmonary disorder due to chronic cigarette smoking, and severe asthma on chronic prednisone therapy presented with recurrent intractable abdominal pain and shortness of breath. The patient underwent esophagogastroduodenoscopy (EGD) showing friable mucosa returning positive for Strongyloides stercoralis infection. The patient deteriorated with progressive acute hypoxic respiratory failure and acute metabolic encephalopathy requiring invasive mechanical ventilation. Dual antiparasitic therapy with ivermectin and albendazole was initiated, and the patient was treated for septic shock. The patient was successfully extubated and was discharged from the hospital to a rehabilitation center without steroid therapy. Due to the classic transmission and life cycle of the filiform larvae, the lungs are target organs in HS. The mortality of Strongyloides HS ranges from 85% to 100% when untreated. HS due to Strongyloides stercoralis carries a high risk for disseminated infection in patients with chronic steroids. High index of suspicion, tissue sample, and prompt institution of target therapy institutions are key for a successful clinical outcome.